1981
DOI: 10.1109/tit.1981.1056305
|View full text |Cite
|
Sign up to set email alerts
|

On Lewis' simulation method for point processes

Abstract: When dealing with classical spike train analysis, the practitioner often performs goodness-of-fit tests to test whether the observed process is a Poisson process, for instance, or if it obeys another type of probabilistic model (Yana et al. in Biophys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
493
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 627 publications
(496 citation statements)
references
References 16 publications
1
493
0
2
Order By: Relevance
“…Ogata [34] shown that the log likelihood can be computed recursively reducing computational complexity to O(N).…”
Section: Discussionmentioning
confidence: 99%
“…Ogata [34] shown that the log likelihood can be computed recursively reducing computational complexity to O(N).…”
Section: Discussionmentioning
confidence: 99%
“…This is demonstrated in the example in Figure 2.1 below. This simulation, in addition to all the others throughout this work, is constructed by use of the algorithm described in Ogata [21]. , β = 1, and λ * = 1.…”
Section: Comparison To the Poisson Processmentioning
confidence: 99%
“…In each example we derive the simulated functions via 100,000 replications of the procedure described in Ogata [21]. We start with the mean and variance of a single phase system, as shown in the pair of plots below in Figure 3 , λ * = µ = 1.…”
Section: Simulation Studymentioning
confidence: 99%
“…Note also that simulation algorithms of Hawkes processes are easily available (see e.g. Ogata, 1981;Moller and Rasmussen, 2005, and Appendix A), allowing further developments for the use of the estimated models. These practical properties make Hawkes processes good candidates for the study of the clustering of events empirically observed in order book models (Hautsch, 2004;Bowsher, 2007;Large, 2007;Bacry et al, 2012).…”
Section: Testing the Calibrationmentioning
confidence: 99%
“…Appendix A -Simulation of Hawkes processes Ogata (1981) proposes an algorithm for the simulation of Hawkes processes, based on a general procedure called thinning. Taking a different point of view, a more recent work by Moller and Rasmussen (2005) claims to provide better quality simulations, without edge effects.…”
mentioning
confidence: 99%